Dynamics and determinants of rural associativity strengthening: the case of Colombia - Benson, Allison; Zamora-Duque, Adrián (REVESCO. Revista de Estudios Cooperativos, 2023)
Rural associativity is key for rural development, allowing producers, through collective action, to profit from economies of scale to improve their access to markets, information, technology, and support. Despite its relevance, there is little information on the characteristics and needs of rural producer organizations in Colombia. In this article, we elaborate a detailed productive, commercial, financial, organizational, and administrative diagnosis of 54 organizations in Colombia that received a process of technical and business strengthening. We estimate a probabilistic model to identify the organizational characteristics that increase the probability of observing greater improvements. The results show significant increases in the level of maturation of the organizations, especially in their productive and commercial capacities, precisely in which the greatest initial weaknesses were evident. We found that being an association, having a woman as a leader, and having been established for more years, increases the probability of observing greater improvements. We also identify the specific processes of organizational functioning that improve after strengthening and the program activities that potentially explain each improvement. Our results contribute to understanding the mechanisms that explain the effective strengthening of rural associativity.